Menumbuhkan Budaya Literasi Membaca Dengan Menciptakan Lingkungan Literasi Di Sekolah Dasar Islam Plus YLPI Pekanbaru - Raihanatu Binqalbi Ruzain; Zulkifli Zulkifli; Zulrafli Zulrafli; Rosyida Rosyida; Annisa Salsabila; Dede Suhada; Rangga Adhitya Rosman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The National Literacy Movement (GLN) carried out by the ministry of education and culture in 2016 aims to foster a culture of literacy in the school, home, and community by building reading corners at schools, reading gardens, regional libraries, and the Atmazaki smart house. The community service activities aim to offer and present interesting activities to foster a culture of reading literacy in students by building reading corners, reading programs 15 minutes before formal learning, and educating the importance of literacy. This type of service is descriptive using a qualitative approach. The sample consisted of 51 students of YLPI Plus Islamic Elementary School consisting of 21 female students and 30 male students. Collecting data using interviews, observation, and documentation. The results of the dedication are implementing literacy through the storytelling method, reading for 15 minutes before formal learning, and always taking the time to read in the reading corner. The dedication concludes that students are the criteria for those who like to read and all these activities have been well followed by students.